A composite water-based film heat-sealing adhesive and preparation method thereof

By using specific raw materials and flame retardants in the aqueous film heat sealant, a composite water-based film heat sealant with high bonding strength, water resistance and flame retardant is prepared, which solves the problem of insufficient performance of the existing heat sealant.

CN118813192BActive Publication Date: 2025-03-18JINHUA QISHENG NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411309942.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-03-18
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The comprehensive performance of existing water-based film heat sealing glue is poor, making it difficult to meet the high requirements of packaging materials for bonding strength, water resistance and flame retardancy.

Method used

Toluene diisocyanate, polycarbonate diol and 2,2-dihydroxymethylpropionic acid are used as raw materials to prepare flame retardant aqueous polyurethane, and reactive phosphorus-based flame retardant and ethylene acrylic acid copolymer are added during the chain extension process to improve the performance of the heat sealant through the design of composite materials.

Benefits of technology

It significantly improves the flame retardant properties, water resistance and bonding strength of heat sealing glue, and enhances its stability and application fields in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of heat-sealing adhesives, and in particular to a composite water-based thin-film heat-sealing adhesive and a preparation method thereof. The invention discloses an ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, which has excellent ultraviolet light aging resistance and a stable and lasting bonding effect. The ethylene acrylic acid copolymer is added into a flame-retardant water-based polyurethane to prepare the composite water-based thin-film heat-sealing adhesive, which can ensure that a good bonding effect can be achieved on surfaces of different materials, and can also optimize the heat-sealing and flame-retardant properties of the thin-film heat-sealing adhesive by combining the flame-retardant properties of the flame-retardant water-based polyurethane, so as to ensure that a stable, firm and flame-retardant sealing layer is formed during the heat-sealing process; secondly, the ethylene acrylic acid copolymer can interact with a flame retardant through a specific group or segment in its molecular structure, so as to further improve the flame-retardant properties of the heat-sealing adhesive, so that the prepared composite water-based thin-film heat-sealing adhesive has a wider application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat-sealing adhesives, and in particular to a composite water-based thin-film heat-sealing adhesive and a preparation method thereof. Background Art

[0002] With the rapid development of the packaging industry, the demand for packaging materials is increasing, especially in the fields of food, medicine and electronic products, which puts forward higher requirements on the environmental protection, safety and functionality of packaging materials. Traditional heat seal adhesives mostly use organic solvents as carriers, which not only have large odor and pollution problems during production and use, but also increase production costs and environmental protection treatment difficulties. Therefore, it is particularly important to develop an environmentally friendly, efficient and excellent performance water-based film heat seal adhesive.

[0003] The existing water-based film heat sealant uses water as the dispersion medium and is prepared through scientific formulas and advanced processes. It can solve the environmental problems of traditional heat sealants and provide new solutions for the packaging materials industry. If its comprehensive performance can be improved on this basis, such as improving bonding strength, water resistance and flame retardancy, the application field of water-based heat sealants can be greatly expanded. Summary of the invention

[0004] Technical issues solved

[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a composite water-based thin film heat-sealing adhesive and a preparation method thereof, which can effectively solve the problem of poor comprehensive performance of the heat-sealing adhesive ring in the prior art.

[0006] Technical Solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A method for preparing a composite water-based thin film heat-sealing adhesive, the preparation method comprising:

[0009] S1. A polyurethane prepolymer is prepared using toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials, and a reactive phosphorus flame retardant is added during the chain extension process to react and obtain a flame-retardant waterborne polyurethane;

[0010] S2, preparing ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, and dissolving ammonium polyphosphate in deionized water to prepare a saturated ammonium polyphosphate solution;

[0011] S3. Add 1-2 parts by weight of saturated ammonium polyphosphate solution to 100 parts by weight of flame-retardant waterborne polyurethane, disperse evenly and pour into a reaction kettle, add 22-25 parts by weight of ethylene acrylic acid copolymer and 8-10 parts by weight of epoxy resin, stir and disperse at a temperature of 120°C, and the result is a composite water-based thin film heat-sealing adhesive.

[0012] Furthermore, in S1, the preparation steps of the reactive phosphorus-based flame retardant are:

[0013] Step 1, dissolving 0.05 mol of calculated amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in 50 mL of dichloromethane, stirring and dispersing it uniformly as the first component, dissolving 0.05 mol of calculated amount of p-hydroxybenzaldehyde in 50 mL of dichloromethane, and dispersing it ultrasonically as the second component;

[0014] Step 2: Pour the second component into the first component and react at 85° C. for 4 hours to obtain a reactive phosphorus flame retardant.

[0015] Furthermore, the specific operation of stirring and dispersing uniformly in step one is stirring at a speed of 500 r / min for 10 minutes, and the specific operation of ultrasonic dispersion in step one is ultrasonic dispersion at a frequency of 26 kHz for 10 minutes.

[0016] Furthermore, in S1, the preparation steps of the flame retardant waterborne polyurethane are:

[0017] Step 1, weigh 70g of polycarbonate diol and place it at 120℃ and 0.1MPa for 2.5h of rotary evaporation, then pour it into a flask and heat it in an oil bath at 80℃, stir evenly, add 12g of toluene diisocyanate and react for 1h, cool to 75℃, add 3g of 2,2-dihydroxymethylpropionic acid and 0.3mL of dibutyltin dilaurate and continue to react for 3h, the result is recorded as the pre-reaction component;

[0018] Step 2: Add 2g of 1,4-butanediol to the pre-reaction components and react for 1h, then cool to 35°C, then add 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 5g of reactive phosphorus flame retardant, react at 65°C for 2h, then add 3g of triethylamine, stir at 800r / min for 5min, then add 25-30g of deionized water for high-speed emulsification and dispersion, and distill under reduced pressure at 58°C to obtain a flame-retardant waterborne polyurethane.

[0019] Furthermore, the specific operation of uniform stirring in step 1 is stirring at a speed of 300 r / min for 30 min, and the specific operation of high-speed emulsification and dispersion in step 2 is stirring at a speed of 1500 r / min for 30 min.

[0020] Furthermore, in S2, the preparation steps of ethylene acrylic acid copolymer are:

[0021] Step A, weighing 1600g of deionized water, 300g of tert-butyl alcohol and 30g of acrylic acid solution into a reaction kettle, degassing, displacing and eluting with ethylene at a pressure of 0.68MPa twice, then filling with ethylene to a pressure of 6.2MPa, heating to 80°C under stirring conditions, and the obtained mixture is recorded as a mixed component;

[0022] Step B, pumping 15-20 mL of potassium persulfate solution into the mixed components and introducing ethylene until the pressure reaches 20 MPa, adding 16-18 mL of potassium persulfate solution after reacting for 1 hour, and continuing the reaction for 6 hours, continuously adding ethylene during the reaction to maintain the pressure in the reactor at 13-15 MPa, continuing the reaction until the solid content reaches 20%, cooling the reactor to terminate the reaction, and the obtained product is recorded as the reaction product;

[0023] Step C, add 200-260 mL of deionized water to 100 mL of the reaction product, add sodium hydroxide solution under stirring to adjust the pH value to 9-10, then add 2-3 g of sodium chloride and continue stirring for 30 minutes, and the obtained product is recorded as the product to be purified;

[0024] Step D: add hydrochloric acid solution to the product to be purified under stirring to adjust the pH value to 2-3, raise the temperature to 50°C and continue stirring for 10 minutes, then let it stand for 2 hours, filter to obtain a filter cake, and dry the filter cake under air flow to obtain ethylene acrylic acid copolymer.

[0025] Furthermore, the stirring speed in step A is 500 r / min, the mass fraction of the potassium persulfate solution in step B is 5%, the stirring speed in step C is 300 r / min, the mass fraction of the sodium hydroxide solution in step C is 10%, the stirring speed in step D is 200 r / min, and the mass fraction of the hydrochloric acid solution in step D is 20%.

[0026] Furthermore, in S2, the preparation method of the saturated ammonium polyphosphate solution is: add 1g of ammonium polyphosphate to 10g of deionized water, stir at a speed of 500r / min for 5min, and then continue to add ammonium polyphosphate, with the weight of each addition being 0.3g, until undissolved ammonium polyphosphate appears, and after filtering out the undissolved ammonium polyphosphate, the resulting solution is a saturated ammonium polyphosphate solution.

[0027] Furthermore, the specific operation of uniform dispersion in S3 is stirring at a rotation speed of 600 r / min for 10 min, and the specific operation of stirring and dispersing in S3 is stirring at a rotation speed of 500 r / min for 10 min.

[0028] A composite water-based thin-film heat-sealing adhesive is prepared by a preparation method of the composite water-based thin-film heat-sealing adhesive.

[0029] Beneficial Effects

[0030] The present invention provides a composite water-based thin film heat-sealing adhesive and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention uses toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials to prepare polyurethane prepolymer, and adds reactive phosphorus flame retardant in the chain extension process to prepare flame retardant waterborne polyurethane, which can make the prepared flame retardant waterborne polyurethane have stable flame retardant performance and good water resistance on the basis of high decomposition temperature; due to the introduction of polycarbonate diol, the prepared flame retardant waterborne polyurethane has good weather resistance and can still maintain stable performance in harsh environment, and toluene diisocyanate can react with The polycarbonate diol forms a strong polyurethane chain segment, and the chain extension effect of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane can further enhance the interaction between molecules, so that the prepared flame-retardant waterborne polyurethane has good tensile strength and tear strength; secondly, the derivative of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, that is, the reactive phosphorus flame retardant, is introduced into the flame-retardant waterborne polyurethane through a chain extender, so that it can cooperate with ammonium polyphosphate to further enhance the flame retardant properties of the prepared heat-sealing adhesive.

[0032] 2. The ethylene acrylic acid copolymer of the present invention, which is prepared from tert-butyl alcohol, acrylic acid and ethylene as raw materials, has excellent resistance to ultraviolet aging and stable and lasting bonding effect. When the ethylene acrylic acid copolymer is added to the flame-retardant waterborne polyurethane to prepare a composite water-based thin film heat-sealing adhesive, it can ensure that a good bonding effect can be achieved on the surfaces of different materials. In addition, the flame-retardant property of the flame-retardant waterborne polyurethane can be combined to optimize the heat-sealing property and flame-retardant property of the thin film heat-sealing adhesive, ensuring that a stable, firm and flame-retardant sealing layer is formed during the heat-sealing process. Secondly, the ethylene acrylic acid copolymer can interact with the flame retardant through specific groups or segments in its molecular structure, further improving the flame-retardant property of the heat-sealing adhesive, so that the prepared composite water-based thin film heat-sealing adhesive has a wider application field. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Example 1

[0036] A preparation method of a composite water-based thin film heat-sealing adhesive in this embodiment is as follows:

[0037] S1. A polyurethane prepolymer is prepared using toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials, and a reactive phosphorus flame retardant is added during the chain extension process to react and obtain a flame-retardant waterborne polyurethane;

[0038] The preparation steps of the reactive phosphorus flame retardant are as follows:

[0039] Step 1, 0.05 mol of calculated amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was dissolved in 50 mL of dichloromethane, stirred at a speed of 500 r / min for 10 min, and recorded as the first component; 0.05 mol of calculated amount of p-hydroxybenzaldehyde was dissolved in 50 mL of dichloromethane, and ultrasonically dispersed at a frequency of 26 kHz for 10 min, and recorded as the second component;

[0040] Step 2: Pour the second component into the first component and react at 85° C. for 4 hours to obtain a reactive phosphorus flame retardant.

[0041] The preparation steps of flame retardant waterborne polyurethane are as follows:

[0042] Step 1, weigh 70g of polycarbonate diol and place it at 120℃ and 0.1MPa for 2.5h by rotary evaporation, then pour it into a flask and heat it in an oil bath at 80℃, stir it at 300r / min for 30min, add 12g of toluene diisocyanate and react for 1h, cool it to 75℃, add 3g of 2,2-dihydroxymethylpropionic acid and 0.3mL of dibutyltin dilaurate and continue to react for 3h, the result is recorded as the pre-reaction component;

[0043] Step 2: Add 2g of 1,4-butanediol to the pre-reaction components, react for 1h, then cool to 35°C, then add 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 5g of reactive phosphorus flame retardant, react at 65°C for 2h, add 3g of triethylamine, stir at 800r / min for 5min, add 28g of deionized water, stir at 1500r / min for 30min, and distill under reduced pressure at 58°C to obtain a flame-retardant waterborne polyurethane.

[0044] S2, preparing ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, and dissolving ammonium polyphosphate in deionized water to prepare a saturated ammonium polyphosphate solution;

[0045] Wherein, the preparation steps of ethylene acrylic acid copolymer are:

[0046] Step A, weighing 1600g of deionized water, 300g of tert-butyl alcohol and 30g of acrylic acid solution into a reaction kettle, degassing, displacing and eluting with ethylene at a pressure of 0.68MPa twice, then filling with ethylene to a pressure of 6.2MPa, heating to 80°C under stirring at a speed of 500r / min, and recording the obtained mixture as a mixed component;

[0047] Step B, pumping 18 mL of 5% potassium persulfate solution into the mixed components and introducing ethylene until the pressure reaches 20 MPa, adding 17 mL of 5% potassium persulfate solution after reacting for 1 hour, and continuing the reaction for 6 hours, continuously adding ethylene during the reaction to maintain the pressure in the reactor at 14 MPa, continuing the reaction until the solid content reaches 20%, cooling the reactor to terminate the reaction, and the obtained product is recorded as the reaction product;

[0048] Step C, add 230 mL of deionized water to 100 mL of the reaction product, add a 10% sodium hydroxide solution with a stirring speed of 300 r / min to adjust the pH value to 10, then add 3 g of sodium chloride and continue stirring for 30 min, and the result is recorded as the product to be purified;

[0049] Step D: add a 20% hydrochloric acid solution to the product to be purified under stirring at a speed of 200 r / min to adjust the pH value to 2, raise the temperature to 50° C. and continue stirring for 10 min, then let it stand for 2 h, filter to obtain a filter cake, and dry the filter cake under air flow to obtain ethylene acrylic acid copolymer.

[0050] The preparation method of the saturated ammonium polyphosphate solution is as follows: add 1g of ammonium polyphosphate to 10g of deionized water, stir at a speed of 500r / min for 5min, and then continue to add ammonium polyphosphate, with the weight of each addition being 0.3g, until undissolved ammonium polyphosphate appears. After filtering out the undissolved ammonium polyphosphate, the result is a saturated ammonium polyphosphate solution.

[0051] S3. Add 2 parts by weight of saturated ammonium polyphosphate solution to 100 parts by weight of flame-retardant waterborne polyurethane, stir at a speed of 600 r / min for 10 minutes, pour into a reactor, add 24 parts by weight of ethylene acrylic acid copolymer and 9 parts by weight of epoxy resin, stir at a speed of 500 r / min for 10 minutes at a temperature of 120°C, and the result is a composite water-based thin film heat-sealing adhesive.

[0052] A composite water-based thin-film heat-sealing adhesive is prepared by a preparation method of the composite water-based thin-film heat-sealing adhesive.

[0053] Example 2

[0054] A preparation method of a composite water-based thin film heat-sealing adhesive in this embodiment is as follows:

[0055] S1. A polyurethane prepolymer is prepared using toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials, and a reactive phosphorus flame retardant is added during the chain extension process to react and obtain a flame-retardant waterborne polyurethane;

[0056] The preparation steps of the reactive phosphorus flame retardant are as follows:

[0057] Step 1, 0.05 mol of calculated amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was dissolved in 50 mL of dichloromethane, stirred at a speed of 500 r / min for 10 min, and recorded as the first component; 0.05 mol of calculated amount of p-hydroxybenzaldehyde was dissolved in 50 mL of dichloromethane, and ultrasonically dispersed at a frequency of 26 kHz for 10 min, and recorded as the second component;

[0058] Step 2: Pour the second component into the first component and react at 85° C. for 4 hours to obtain a reactive phosphorus flame retardant.

[0059] The preparation steps of flame retardant waterborne polyurethane are as follows:

[0060] Step 1, weigh 70g of polycarbonate diol and place it at 120℃ and 0.1MPa for 2.5h by rotary evaporation, then pour it into a flask and heat it in an oil bath at 80℃, stir it at 300r / min for 30min, add 12g of toluene diisocyanate and react for 1h, cool it to 75℃, add 3g of 2,2-dihydroxymethylpropionic acid and 0.3mL of dibutyltin dilaurate and continue to react for 3h, the result is recorded as the pre-reaction component;

[0061] Step 2: Add 2g of 1,4-butanediol to the pre-reaction component and react for 1h, then cool to 35°C, then add 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 5g of reactive phosphorus flame retardant, react at 65°C for 2h, add 3g of triethylamine, stir at 800r / min for 5min, add 25g of deionized water, stir at 1500r / min for 30min, and distill under reduced pressure at 58°C to obtain a flame-retardant waterborne polyurethane.

[0062] S2, preparing ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, and dissolving ammonium polyphosphate in deionized water to prepare a saturated ammonium polyphosphate solution;

[0063] Wherein, the preparation steps of ethylene acrylic acid copolymer are:

[0064] Step A, weighing 1600g of deionized water, 300g of tert-butyl alcohol and 30g of acrylic acid solution into a reaction kettle, degassing, displacing and eluting with ethylene at a pressure of 0.68MPa twice, then filling with ethylene to a pressure of 6.2MPa, heating to 80°C under stirring at a speed of 500r / min, and recording the obtained mixture as a mixed component;

[0065] Step B, pumping 15 mL of 5% potassium persulfate solution into the mixed components and introducing ethylene until the pressure reaches 20 MPa, adding 16 mL of 5% potassium persulfate solution after reacting for 1 hour, and continuing the reaction for 6 hours, continuously adding ethylene during the reaction to maintain the pressure in the reactor at 13 MPa, continuing the reaction until the solid content reaches 20%, cooling the reactor to terminate the reaction, and the obtained product is recorded as the reaction product;

[0066] Step C, add 200 mL of deionized water to 100 mL of the reaction product, add a 10% sodium hydroxide solution with a stirring speed of 300 r / min to adjust the pH value to 9, then add 2 g of sodium chloride and continue stirring for 30 min, and the result is recorded as the product to be purified;

[0067] Step D: add a 20% hydrochloric acid solution to the product to be purified under stirring at a speed of 200 r / min to adjust the pH value to 2, raise the temperature to 50° C. and continue stirring for 10 min, then let it stand for 2 h, filter to obtain a filter cake, and dry the filter cake under air flow to obtain ethylene acrylic acid copolymer.

[0068] The preparation method of the saturated ammonium polyphosphate solution is as follows: add 1g of ammonium polyphosphate to 10g of deionized water, stir at a speed of 500r / min for 5min, and then continue to add ammonium polyphosphate, with the weight of each addition being 0.3g, until undissolved ammonium polyphosphate appears. After filtering out the undissolved ammonium polyphosphate, the result is a saturated ammonium polyphosphate solution.

[0069] S3. Add 1 part by weight of saturated ammonium polyphosphate solution to 100 parts by weight of flame-retardant waterborne polyurethane, stir at a speed of 600 r / min for 10 minutes, pour into a reactor, add 22 parts by weight of ethylene acrylic acid copolymer and 8 parts by weight of epoxy resin, stir at a speed of 500 r / min for 10 minutes at a temperature of 120°C, and the result is a composite water-based thin film heat-sealing adhesive.

[0070] A composite water-based thin-film heat-sealing adhesive is prepared by a preparation method of the composite water-based thin-film heat-sealing adhesive.

[0071] Example 3

[0072] A preparation method of a composite water-based thin film heat-sealing adhesive in this embodiment is as follows:

[0073] S1. A polyurethane prepolymer is prepared using toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials, and a reactive phosphorus flame retardant is added during the chain extension process to react and obtain a flame-retardant waterborne polyurethane;

[0074] The preparation steps of the reactive phosphorus flame retardant are as follows:

[0075] Step 1, 0.05 mol of calculated amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was dissolved in 50 mL of dichloromethane, stirred at a speed of 500 r / min for 10 min, and recorded as the first component; 0.05 mol of calculated amount of p-hydroxybenzaldehyde was dissolved in 50 mL of dichloromethane, and ultrasonically dispersed at a frequency of 26 kHz for 10 min, and recorded as the second component;

[0076] Step 2: Pour the second component into the first component and react at 85° C. for 4 hours to obtain a reactive phosphorus flame retardant.

[0077] The preparation steps of flame retardant waterborne polyurethane are as follows:

[0078] Step 1, weigh 70g of polycarbonate diol and place it at 120℃ and 0.1MPa for 2.5h by rotary evaporation, then pour it into a flask and heat it in an oil bath at 80℃, stir it at 300r / min for 30min, add 12g of toluene diisocyanate and react for 1h, cool it to 75℃, add 3g of 2,2-dihydroxymethylpropionic acid and 0.3mL of dibutyltin dilaurate and continue to react for 3h, the result is recorded as the pre-reaction component;

[0079] Step 2: Add 2g of 1,4-butanediol to the pre-reaction components and react for 1h, then cool to 35°C, then add 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 5g of reactive phosphorus flame retardant, react at 65°C for 2h, add 3g of triethylamine, stir at 800r / min for 5min, add 30g of deionized water, stir at 1500r / min for 30min, and distill under reduced pressure at 58°C to obtain a flame-retardant waterborne polyurethane.

[0080] S2, preparing ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, and dissolving ammonium polyphosphate in deionized water to prepare a saturated ammonium polyphosphate solution;

[0081] Wherein, the preparation steps of ethylene acrylic acid copolymer are:

[0082] Step A, weighing 1600g of deionized water, 300g of tert-butyl alcohol and 30g of acrylic acid solution into a reaction kettle, degassing, displacing and eluting with ethylene at a pressure of 0.68MPa twice, then filling with ethylene to a pressure of 6.2MPa, heating to 80°C under stirring at a speed of 500r / min, and recording the obtained mixture as a mixed component;

[0083] Step B, pumping 20 mL of 5% potassium persulfate solution into the mixed components and introducing ethylene until the pressure reaches 20 MPa, adding 18 mL of 5% potassium persulfate solution after reacting for 1 hour, and continuing the reaction for 6 hours, continuously adding ethylene during the reaction to maintain the pressure in the reactor at 15 MPa, continuing the reaction until the solid content reaches 20%, cooling the reactor to terminate the reaction, and the obtained product is recorded as the reaction product;

[0084] Step C, add 260 mL of deionized water to 100 mL of the reaction product, add a 10% sodium hydroxide solution with a stirring speed of 300 r / min to adjust the pH value to 10, then add 3 g of sodium chloride and continue stirring for 30 min, and the result is recorded as the product to be purified;

[0085] Step D: add a 20% hydrochloric acid solution to the product to be purified under stirring at a speed of 200 r / min to adjust the pH value to 3, raise the temperature to 50° C. and continue stirring for 10 min, then let it stand for 2 h, filter to obtain a filter cake, and dry the filter cake under air flow to obtain ethylene acrylic acid copolymer.

[0086] The preparation method of the saturated ammonium polyphosphate solution is as follows: add 1g of ammonium polyphosphate to 10g of deionized water, stir at a speed of 500r / min for 5min, and then continue to add ammonium polyphosphate, with the weight of each addition being 0.3g, until undissolved ammonium polyphosphate appears. After filtering out the undissolved ammonium polyphosphate, the result is a saturated ammonium polyphosphate solution.

[0087] S3. Add 2 parts by weight of saturated ammonium polyphosphate solution to 100 parts by weight of flame-retardant waterborne polyurethane, stir at a speed of 600 r / min for 10 minutes, pour into a reactor, add 25 parts by weight of ethylene acrylic acid copolymer and 10 parts by weight of epoxy resin, stir at a speed of 500 r / min for 10 minutes at a temperature of 120°C, and the result is a composite water-based thin film heat-sealing adhesive.

[0088] A composite water-based thin-film heat-sealing adhesive is prepared by a preparation method of the composite water-based thin-film heat-sealing adhesive.

[0089] Comparative Example 1

[0090] The composite water-based thin film heat sealant and the preparation method thereof provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 1, the flame-retardant water-based polyurethane in Example 1 is replaced with a water-based polyurethane of model 951.

[0091] Comparative Example 2

[0092] The composite water-based thin film heat sealant and its preparation method provided in this comparative example are substantially the same as those in Example 1, with the main difference being that in this comparative example 2, the ethylene acrylic acid copolymer in Example 1 is replaced with an epoxy resin of model number e44.

[0093] Performance Testing

[0094] The composite water-based thin film heat-sealing adhesives prepared in Examples 1-3 and Comparative Examples 1-2 are marked as Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, respectively. Then, the performance of Examples 1-3 and Comparative Examples 1-2 is tested. The specific testing methods and test items are as follows:

[0095] 1. The tensile properties of Examples 1-3 and Comparative Examples 1-2 were measured using a universal material testing machine in accordance with GB / T1040.1-2006 standard, with a tensile rate of 50 mm / min and a clamp spacing of 25 mm. The obtained data are recorded in the following table;

[0096] 2. The limiting oxygen index of Examples 1-3 and Comparative Examples 1-2 was measured using an oxygen index meter, and the obtained data were recorded in the following table;

[0097] 3. The composite water-based thin film heat seal adhesive prepared in Examples 1-3 and Comparative Examples 1-2 was dried to form an adhesive film, and then the adhesive film was cut into sheets of 2 cm×2 cm×0.5 cm. After being immersed in water for 24 h and 72 h, the weight increase rate was calculated to obtain the water absorption rate. The specific formula is:

[0098] Water absorption = (M1-M0)M0

[0099] Among them, M0 is the mass before immersion, M1 is the mass after immersion, and the obtained data are recorded in the following table.

[0100]

[0101] It can be seen from the data in the above table that the composite water-based film heat-sealing adhesive in Examples 1-3 has a significantly higher limiting oxygen index and a lower water absorption rate than that in Comparative Example 1, indicating that the flame retardant water-based polyurethane prepared in the present invention is used as a raw material to prepare the heat-sealing adhesive, which can significantly improve the flame retardant properties and water resistance of the heat-sealing adhesive. Secondly, the composite water-based film heat-sealing adhesive in Examples 1-3 has a significantly higher tensile strength than that in Comparative Example 2, indicating that adding ethylene acrylic acid copolymer to the flame retardant water-based polyurethane to prepare the heat-sealing adhesive can improve the mechanical properties of the heat-sealing adhesive. In summary, the composite water-based film heat-sealing adhesive prepared by the preparation method of the present invention has better performance and can be applied to a wider market field.

[0102] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite water-based thin film heat sealant, characterized in that: The preparation method is: S1. A polyurethane prepolymer is prepared using toluene diisocyanate, polycarbonate diol and 2,2-dimethylol propionic acid as raw materials, and a reactive phosphorus flame retardant is added during the chain extension process to react and obtain a flame-retardant waterborne polyurethane; S2, preparing ethylene acrylic acid copolymer using tert-butyl alcohol, acrylic acid and ethylene as raw materials, and dissolving ammonium polyphosphate in deionized water to prepare a saturated ammonium polyphosphate solution; S3, add 1-2 parts by weight of saturated ammonium polyphosphate solution to 100 parts by weight of flame-retardant waterborne polyurethane, pour into a reaction kettle after uniform dispersion, add 22-25 parts by weight of ethylene acrylic acid copolymer and 8-10 parts by weight of epoxy resin, stir and disperse at a temperature of 120° C., and the result is a composite waterborne thin film heat seal adhesive; In S1, the preparation steps of the reactive phosphorus-based flame retardant are: Step 1, dissolving 0.05 mol of calculated amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in 50 mL of dichloromethane, stirring and dispersing it uniformly as the first component, dissolving 0.05 mol of calculated amount of p-hydroxybenzaldehyde in 50 mL of dichloromethane, and dispersing it ultrasonically as the second component; Step 2: Pour the second component into the first component and react at 85°C for 4 hours to obtain a reactive phosphorus flame retardant. In S1, the preparation steps of the flame retardant waterborne polyurethane are: Step 1, weigh 70g of polycarbonate diol and place it at 120℃ and 0.1MPa for 2.5h of rotary evaporation, then pour it into a flask and heat it in an oil bath at 80℃, stir evenly, add 12g of toluene diisocyanate and react for 1h, cool to 75℃, add 3g of 2,2-dihydroxymethylpropionic acid and 0.3mL of dibutyltin dilaurate and continue to react for 3h, the result is recorded as the pre-reaction component; Step 2: Add 2g of 1,4-butanediol to the pre-reaction components and react for 1h, then cool to 35°C, then add 4g of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane and 5g of reactive phosphorus flame retardant, react at 65°C for 2h, then add 3g of triethylamine, stir at 800r / min for 5min, then add 25-30g of deionized water for high-speed emulsification and dispersion, and distill under reduced pressure at 58°C to obtain a flame-retardant waterborne polyurethane.

2. The method for preparing a composite water-based thin film heat sealant according to claim 1, characterized in that: The specific operation of stirring and dispersing uniformly in step one is stirring at a speed of 500 r / min for 10 min, and the specific operation of ultrasonic dispersion in step one is ultrasonic dispersion at a frequency of 26 kHz for 10 min.

3. The method for preparing a composite water-based thin film heat sealant according to claim 1, characterized in that: The specific operation of stirring evenly in step 1 is stirring at a speed of 300 r / min for 30 min, and the specific operation of high-speed emulsification and dispersion in step 2 is stirring at a speed of 1500 r / min for 30 min.

4. The method for preparing a composite water-based thin film heat sealant according to claim 1, characterized in that: In S2, the preparation steps of ethylene acrylic acid copolymer are: Step A, weighing 1600g of deionized water, 300g of tert-butyl alcohol and 30g of acrylic acid solution into a reaction kettle, degassing, displacing and eluting with ethylene at a pressure of 0.68MPa twice, then filling with ethylene to a pressure of 6.2MPa, heating to 80°C under stirring conditions, and the obtained mixture is recorded as a mixed component; Step B, pumping 15-20 mL of potassium persulfate solution into the mixed components and introducing ethylene until the pressure reaches 20 MPa, adding 16-18 mL of potassium persulfate solution after reacting for 1 hour, and continuing the reaction for 6 hours, continuously adding ethylene during the reaction to maintain the pressure in the reactor at 13-15 MPa, continuing the reaction until the solid content reaches 20%, cooling the reactor to terminate the reaction, and the obtained product is recorded as the reaction product; Step C, add 200-260 mL of deionized water to 100 mL of the reaction product, add sodium hydroxide solution under stirring to adjust the pH value to 9-10, then add 2-3 g of sodium chloride and continue stirring for 30 minutes, and the obtained product is recorded as the product to be purified; Step D, adding hydrochloric acid solution to the product to be purified under stirring to adjust the pH value to 2-3, heating to 50° C. and continuing stirring for 10 min, then standing for 2 h, filtering to obtain a filter cake, and drying the filter cake under air flow to obtain an ethylene acrylic acid copolymer; 5. The method for preparing a composite water-based thin film heat sealant according to claim 4, characterized in that: The stirring condition in step A is at a rotation speed of 500 r / min, the mass fraction of the potassium persulfate solution in step B is 5%, the stirring condition in step C is at a rotation speed of 300 r / min, the mass fraction of the sodium hydroxide solution in step C is 10%, the stirring condition in step D is at a rotation speed of 200 r / min, and the mass fraction of the hydrochloric acid solution in step D is 20%.

6. The method for preparing a composite water-based thin film heat sealant according to claim 1, characterized in that: In S2, the preparation method of the saturated ammonium polyphosphate solution is: add 1g of ammonium polyphosphate to 10g of deionized water, stir at a speed of 500r / min for 5min, and then continue to add ammonium polyphosphate, with the weight of each addition being 0.3g, until undissolved ammonium polyphosphate appears. After filtering out the undissolved ammonium polyphosphate, the result is a saturated ammonium polyphosphate solution.

7. The method for preparing a composite water-based thin film heat sealant according to claim 1, characterized in that: The specific operation of uniform dispersion in S3 is stirring at a speed of 600 r / min for 10 min, and the specific operation of stirring and dispersing in S3 is stirring at a speed of 500 r / min for 10 min.

8. A composite water-based thin film heat sealant, characterized in that: The composite water-based thin film heat-sealing adhesive is prepared by the preparation method of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Phosphaphenanthrene group modified zirconium phosphate-based flame retardant and preparation method thereof

    CN110894369A

  • Oil-resistant B1-grade electron beam irradiation crosslinking low-smoke halogen-free flame-retardant polyolefin sheath material

    CN118185169A